THE ROLE OF NAZHIR IN DEVELOPING WAQF - Faisal Faisal (Proceeding International Seminar of Islamic Studies, 2023)
Waqf property given by the wakif as a form of worship can be used for various activities. However, the development of the waqf has not been carried out optimally. For this reason, the role of nazhir is needed in developing waqf so that it can be managed and utilized for the welfare of the community. This research is a normative juridical research sourced from secondary data and uses documentation studies as a data collection tool. Nazhir has an important role in the development of waqf assets so that the benefits of waqf can reach the needs of the community. Nazhir as waqf manager, participate in maintaining and developing waqf property. Nazhir plays a role in empowering waqf assets and making maximum use of waqf assets, so that the benefits can reach the welfare needs of the community. The development of productive waqf is carried out in a directed and sustainable manner. The development of waqf assets is carried out in order to maximize the benefits of waqf in order to improve the welfare of the community.